“Não tem que dar prioridade para presos não, tem que dar prioridade para a sociedade”: uma análise das medidas de prevenção, controle e combate à COVID-19 no sistema prisional brasileiro - Silva, Adrianne Cristhine Barbosa da (2022)
The brazilian prison system is widely denounced for the violation of human rights and poor conditions for survival, marked by overcrowding, unsanitary prison units and the truculence of State agents. During the COVID-19 pandemic, during which this study was built, changes and decision-making by the State interfered in the lives of the entire population of the country. With the prevention slogans “Stay at home” and “Wash your hands”, the pandemic opened up and deepened the structuring dimensions of social inequality in Brazil, a scenario evidenced in the context of the prison system. Immersed in this context, this research aimed to analyze, theoretically and methodologically based on Socio-Historical Psychology, the measures to prevent, control and combat COVID-19 proposed and/or implemented by the Brazilian State regarding the prison system. A documentary research was carried out, in which the data collection methodology was the cataloging of news, from the periods of February 2020 to June 2021, in the Infovírus and Covid Nas Prisões bases, both engaged with the fight for the rights of the prison population . Of the 534 news found, 169 were selected from the State's action in relation to COVID-19 and made up the final database of this dissertation. These news were separated into four central themes, which indicate the main measures to prevent, control and combat COVID-19 in the prison system, namely: suspension of visits, expansion of the number of vacancies, Recommendation No. 62/2020 (CNJ) and vaccination. In all axes, the policy of death perpetuated in Brazil in the prison system was evidenced, aggravated by the sanitary measures of disorganization and neglect of the current government with the pandemic. This systematization made it possible to apprehend some aspects of the subjective dimension of these measures, namely: ideology of social defense, the process of subjecting the prisoner and the naturalization of the neutrality of the State. On the face of it, the Executive and the Judiciary, especially the National Council of Justice, were going against the grain; however, both followed the logic of mass incarceration and the Democratic State of Criminal Law, guaranteeing the maintenance of the prison system as a fundamental part of the reproduction of capitalism. In addition, the role played by civil society deserves to be highlighted, especially in the figure of women and mothers of prisoners, who fought hard against the hegemonic political project for the prison system. It was concluded that the position adopted by the Brazilian State in prisons is historically constructed and, during the pandemic, the maintenance of the ideology that sows the structuring dimensions of social inequality and perpetuates the practices of torture and human rights violations towards the black, poor and peripheral population